Seaweed flora of the St. Martin’s Reef, Bangladesh (Bangladesh Journal of Plant Taxonomy, 2023)
St. Martin’s Reef (SMR) about 14 km west of the St. Martin’s Island, Teknaf, Cox’s Bazar, Bangladesh was not known during last over 50 years of seaweed researches. Recent six collections made with the assistance of Bangladesh Navy revealed 8 seaweeds species which are Pterocladiella maribagoensis Boo and Geraldo, Hypnea spinella (C. Agardh) Kützing, Peyssonnelia polymorpha (Zonars.) Schmitz, Jania pumila Lamx.,  Jania ungulata f. brevior (Yendo) Dawson (Rhodophyta); Caulerpa racemosa var. clavifera (Turner) Bosse, Bryopsis plumosa (Huds.) C. Ag. and Halimeda tuna (Lin.) Lamx. (Chlorophyta). Of these six seaweeds such as Pterocladiella maribagoensis Boo et Geraldino, Hypnea spinella (C. Agardh) Kützing,  Jania pumila Lamx., Jania ungulata f. brevior (Yendo) Dawson,  Bryopsis plumosa (Huds.) C. Ag. and Halimeda tuna (Lin.) Lamx have been newly recorded and described from the SMR in Bay of Bengal (Bangladesh territory). Presence of Peyssonnelia polymorpha and Bryopsis plumosa in the collections and physical and chemical water environments recorded indicated it as a true newly forming reef. The present illustrated account is however may be considered as base-line information on seaweed flora of the new SMR in the North-east Bangladesh coast. A total of six seaweeds have been newly recorded making the total seaweeds to 215 mostly from the SMI and nearby SMR.Bangladesh J. Plant Taxon. 30(1): 153-163, 2023 (June)